Molecular characterization of Trichuris species isolated from humans, dogs and cats in a rural community in Peninsular Malaysia - Mohd-Shaharuddin, Norashikin; Lim, Yvonne Ai Lian; Hassan, Nur Amirah; Nathan, Sheila; Ngui, Romano (Elsevier, 2019)
Trichuris trichiura (whipworm) are soil-transmitted helminths (STHs) that causing trichuriasis in human. Trichuris vulpis, a canine whipworm has also been reported occasionally in humans. However, an overlapping dimension in the morphology and due to limited external characters between both species may lead to the potential for misidentification. Although there has been an extensive study on the distribution of whipworm in both human and animal hosts, little is known about the molecular epidemiology of Trichuris species in both hosts. To investigate to characterize the whipworm species and to determine the genetic relationship between species infecting both humans and animals, we sequenced the small subunit ribosomal RNA (SSU rRNA) regions of Trichuris egg isolated from humans, dogs and cats in a rural community in Malaysia. A total of 524 fresh fecal samples were collected from humans and animals. The overall prevalence of Trichuris was 59.9% as determined by microscopy examination. The molecular analysis showed that 98.7% were identified as T. trichiura in the human fecal sample. Interestingly, 1.3% were identified as T. vulpis. As for animal fecal sample, 56.8% and 43.2% were identified as T. trichiura and T. vulpis, respectively. Phylogenetic and sequence analysis demonstrated that T. trichiura isolates were genetically distinct from T. vulpis isolates from both hosts. This finding implies that companion animals can be a reservoir and mechanical transmitter for T. trichiura infection in human and also highlighting the possible zoonotic potential of T. vulpis. This finding may also suggest that cross-transmission between humans and animal hosts in sympatric setting may be a source of infection in both hosts. More studies are needed to better understand the transmission dynamic and public health significance of Trichuris infection in both hosts.